Clima organizacional y satisfacción laboral de los colaboradores de la empresa In Excelsis Deo SA en el año 2017 - Mercado Morales, Jorge Luis (2023)
The present study called Organizational Climate and Job Satisfaction of the employees of the company In Excelsis Deo SA in 2017, had the purpose of determining the _x000D_ degree of relationship between the aforementioned variables of the employees of the _x000D_ company In Excelsis Deo SA in 2017 of the city of Trujillo, in order to suggest changes _x000D_ and/or improvements in the company. To carry out this research, the 35 workers that made _x000D_ up the company were studied, applying the survey technique and using as an instrument the questionnaire whose interpretation was under the Likert scale, to diagnose the organizational climate composed of 26 items corresponding to 5 dimensions; and to measure job satisfaction made up of 15 items corresponding to 2 dimensions. To analyze the reliability of the questionnaires, the Cronbach's Alpha coefficient was used for both variables, obtaining the coefficients 0.896 and 0.821, which showed that the questionnaires were reliable. The main hypothesis indicated that there was a relationship between the _x000D_ organizational climate and job satisfaction, which is why, using the Pearson correlation _x000D_ coefficient, it can be affirmed that there is such a positive and significant relationship _x000D_ between both variables. At the level of the specific hypotheses, the dimensions of _x000D_ organizational climate, structure, autonomy and identity were significantly positively _x000D_ correlated with job satisfaction. However, no relationship was found between the reward _x000D_ dimensions and interpersonal relationships with the job satisfaction of the workers under _x000D_ study